2020
DOI: 10.3324/haematol.2019.243543
|View full text |Cite
|
Sign up to set email alerts
|

The regulation and function of CD20: an “enigma” of B-cell biology and targeted therapy

Abstract: The DNA binding site in the MS4A1 promoter has not been defined. NICD: NOTCH1 intracellular domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
175
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(211 citation statements)
references
References 121 publications
(187 reference statements)
1
175
0
4
Order By: Relevance
“…CDK6 was hyper-hydroxymethylated in HPV(−) tumors at seven intronic regions, is targeted in the treatment of certain breast cancers [ 45 ] and recently showed response in the treatment of oral squamous cell carcinoma [ 46 ]. CD20, which is regulated by the epigenetic markers NFκB and SMAD2/3 [ 47 ], is targeted in chronic lymphocytic leukemia and follicular lymphoma [ 48 ]. The NFκB pathway and SMAD2/3 genes were identified as important 5hmC markers in our study, suggesting a potential use of B cell markers in the immunotherapy of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…CDK6 was hyper-hydroxymethylated in HPV(−) tumors at seven intronic regions, is targeted in the treatment of certain breast cancers [ 45 ] and recently showed response in the treatment of oral squamous cell carcinoma [ 46 ]. CD20, which is regulated by the epigenetic markers NFκB and SMAD2/3 [ 47 ], is targeted in chronic lymphocytic leukemia and follicular lymphoma [ 48 ]. The NFκB pathway and SMAD2/3 genes were identified as important 5hmC markers in our study, suggesting a potential use of B cell markers in the immunotherapy of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…BCR signaling propensity is also affected by levels of cell-surface molecules that act as docking sites for positive or negative BCR pathway regulators, which include molecules such as CD19, CD22, and CD32. Recently, we have shown that a notorious therapeutic target in B cell malignancies, CD20, is also a positive BCR signaling regulator ( 28 ). When CD20 is silenced, response to BCR stimulation is weaker, as underscored by the lower phosphorylation of BCR-associated kinases and impaired calcium flux ( 29 , 30 ).…”
Section: Bcr Signaling and Its Cross-talk With Other Pathwaysmentioning
confidence: 99%
“…Ibrutinib with immune modulator lenalidomide and rituximab is under investigation in DLBCL and MCL but has not been successful in CLL ( 178 181 ). A profoundly studied possibility for therapy is combining “BCR inhibitors” with widely-used anti-CD20 monoclonal antibodies ( 28 ). However, adding rituximab to ibrutinib did not bring any clinical benefit and this is likely due to ibrutinib downregulating CD20 levels and/or interfering with effector cell functions ( 28 , 30 , 182 , 183 ).…”
Section: Targeting Ibrutinib Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…16 It is well known that several epigenetic and transcription factors regulate expression of the MS4A1 gene and of the CD20 antigen. 18 Interestingly, mutations of the NOTCH1 intracellular domain lead to accumulation of mutated NOTCH1 in the nucleus and may alter the fine epigenetic regulation of MS4A1 and CD20 expression through interactions with the RBPJ transcription factor that is involved in the NOTCH1 signaling pathway. 16,18 Overall, the biological relationship between NOTCH1 signaling, its deregulation by mutations and expression of CD20 requires further investigation, ideally in study designs aimed at comparing different type 1 and type 2 anti-CD20 mAb in order to understand not only the mechanisms of resistance, but also the strategies to overcome such refractoriness.…”
mentioning
confidence: 99%